2012
DOI: 10.2119/molmed.2012.00010
|View full text |Cite|
|
Sign up to set email alerts
|

MGMT Inhibition Restores ERα Functional Sensitivity to Antiestrogen Therapy

Abstract: Antiestrogen therapy resistance remains a huge stumbling block in the treatment of breast cancer. We have found significant elevation of O 6 methylguanine DNA methyl transferase (MGMT) expression in a small sample of consecutive patients who have failed tamoxifen treatment. Here, we show that tamoxifen resistance is accompanied by upregulation of MGMT. Further we show that administration of the MGMT inhibitor, O 6 -benzylguanine (BG), at nontoxic doses, leads to restoration of a favorable estrogen receptor alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Aberrant proliferation of PD fibroblasts has also been detected in PD patients (28). To inhibit PD fibroblast proliferation, many agents with anti-fibrotic potential have been employed to downregulate or neutralize proliferative, fibrogenic and contractile responses of myofibroblasts (29). Thus, we first investigated the anti-proliferation effect of HS-173 on PD-derived fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant proliferation of PD fibroblasts has also been detected in PD patients (28). To inhibit PD fibroblast proliferation, many agents with anti-fibrotic potential have been employed to downregulate or neutralize proliferative, fibrogenic and contractile responses of myofibroblasts (29). Thus, we first investigated the anti-proliferation effect of HS-173 on PD-derived fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…One cell line study revealed that cells resistant to tamoxifen can be resensitised to its growth-inhibitory effects by targeting and blocking the action of the NF B pathway [165]. Another group suggested that by inhibiting O-6methylguanine-DNA methyltransferase (MGMT), a DNA repair protein they identified as being overexpressed in some tamoxifen resistant cell lines, sensitivity to tamoxifen could be restored [331]. Another reported that a CDK2 inhibitor could reverse endocrine therapy resistance in tumours overexpressing cyclins-E1 and E2 [104].…”
Section: Combating Resistancementioning
confidence: 99%
“…We propose that the augmented turnover of ER in the ER-MGMT complex by fulvestrant also accounts for the enhanced degradation of MGMT we observed in breast cancer cells. The destruction of MGMT in the ER complexes does occur in tamoxifen treated cells, however, to a lower level, as has been implied by previous observations on the ability of BG to overcome tamoxifen resistance [ 28 ] and tamoxifen-induced ubiquitin degradation of MGMT in HT29 cells [ 42 ] . Therefore, our finding on the ability of fulvestrant to trigger MGMT deficiency can be rationally exploited for improved therapy by combining fulvestrant with MGMT-targeted alkylating agents to obtain greater anticancer efficacy.…”
Section: Discussionmentioning
confidence: 69%
“…Previously, a report described the downregulation of MGMT through ubiquitin-proteolysis in tamoxifen treated HT29 cells [ 42 ] . Recently, Bobustuc et al reported a significant upregulation of MGMT in tamoxifen resistant breast cancer cells [ 28 ] . With this background, we sought to determine the estrogenic regulation of MGMT by searching the human MGMT promoter (GenBank: X61657.1) for estrogen response elements and related cis-acting sequences.…”
Section: Resultsmentioning
confidence: 99%